The Relationship Of Community Access Capabilities To Production Forest Products With The Household Welfare Level - Dwi Desriyanti (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2020)
Currently the status of Sanggabuana Forest is a limited production forest located in Mekarbuana Village, Tegalwaru District, Karawang Regency. Communities around the forest can obtain production forest products according to their access capabilities. It is suspected that the higher the ability of community access to production forest products, the higher the level of community household welfare. After conducting research using quantitative and qualitative methods through questionnaires, in-depth interviews and observation of related sources, the condition of the household welfare of the Mekarbuana Village community is quite even and there are no significant gaps. It can be said that there is no relationship between the ability of community access to production forest products and the level of community household welfare.